Managing the relationship between the national government and the provinces. A discussion of provincial environmental initiatives with reference to section 24 of NEMA - Eastwood, Joanna (Department of Public Law, 2014)
This dissertation uses the example of NEMA and the proposed provincial legislation to explore several constitutional issues and is divided into a number of parts. Part II describes the regulatory system provided for in section 24 of NEMA in more detail. Part III discusses the implementation of section 24 of NEMA, with reference to section 85 and section 125 of the Constitution. The latter two sections determine which sphere of government is responsible for the implementation of national legislation that falls within the functional areas listed in Schedule 4 of the Constitution. A related question is whether the national Minister can allocate all the responsibility for implementation of section 24 of NEMA to the provinces. This is what the draft regulations published by the Minister seeks to achieve. Thus, part III of this dissertation considers the constitutionality of the arrangement set up by the Minister in terms of section 24 of NEMA. Part IV of this dissertation provides some background to the proposed provincial legislation and the duplication that would be caused by its simultaneous operation with section 24 of NEMA in the Province. In light of the potential problem of duplication, part IV considers the application of section 146 of the Constitution, which provides a mechanism for resolving conflicts between national and provincial legislation in a Schedule 4 functional area. In particular, it explores whether 'conflict' - when used in the context of section 146 - includes duplication between national and provincial legislation. The principles of co-operative government set out in Chapter 3 of the Constitution are essential in a system of co-operative federalism. The requirements of consultation and co-operation must be brought to bear on the implementation of national legislation such as NEMA and the avoidance of duplicated regulatory systems. The application of co-operative governance principles in this context is discussed in part V.